Improvement of the methodology for determining the movement parameters of individuals with visual impairments during evacuation from higher education institutions with inclusive education using a simplified analytical model - Dotsenko, Oleksandr; Khlevnoi, Oleksandr; Kovalyshyn, Vasyl; Parkhomenko, Volodymyr-Petro; Dyven, Valentyn; Borysova, Anna; Vovk, Sergiy (Eastern-European Journal of Enterprise Technologies, 2024)
The object of the study is the movement parameters of mixed evacuation flows, which include participants with visual impairments. Such parameters are the speed of movement, density and the percentage of participants with visual impairments in the flow. Solving the problems of calculating the duration of evacuation of the population from educational institutions with inclusive education is very relevant, since this process has a significant feature that is not typical for evacuation from most residential and public buildings. In such educational institutions, all students move in groups under the control of scientific and pedagogical workers. This feature is not taken into account in the regulatory documents that fix the methods of calculating the duration of evacuation. The numerical parameters obtained by authors allow to solve this problem. According to the results of the experiment, 241 measurements of the speed and density of the flow were made on horizontal sections, 204 – during the descent of the stairs and 206 – during the ascent. The dependences between these parameters were established by conducting regression analysis. As part of the experiment, flows were monitored with a variable value of the percentage of people with visual impairments in the flow. Thanks to this, the impact of the increase the number of people with visual impairments in the flow on the speed of movement on various sections of the evacuation routes was established. The analysis of the obtained results shows that the appearance of the first participant with visual impairments in the flow leads to a decrease in the speed of movement. In the future, the relationship between a decrease in speed and an increase in the percentage of traffic participants with visual impairments is linear. The obtained dependencies can be used as input parameters for calculations of the duration of evacuation in educational institutions with inclusive education according to a simplified analytical model and allow obtaining smaller deviations from the results obtained in real conditions (3.4–25 %) compared to the current individual model (35, 5–52.3 %)